Implementasi Edukasi Latihan Fisik Pada Lansia Goat Atritis Dengan Gangguan Mobilitas Fisik Di Pusat Pelayanan Sosial Lanjut Usia - Nurul Fazirah Jamaluddin; Bahriah; Sukri (Yayasan Ekselensi Daya Indonesia, 2025)
Gout, or in the medical world called Gout Arthritis, is a joint disease caused by Purine metabolism disorders characterized by high levels of uric acid in the blood. This study aims to describe care for elderly people with gout arthritis with impaired physical mobility at the Elderly Social Service Center. A descriptive case study with case presentations on 2 elderly respondents with Gout Arthritis with impaired physical mobility. The results showed that after implementing elderly exercise for 3 days, both patients experienced a decrease in joint pain complaints. Patients felt fresher and fitter than before doing elderly exercise. Patients' uric acid levels also began to decrease on the third day of elderly exercise. This indicates that elderly exercise is effective in overcoming impaired physical mobility in gout arthritis. This study is recommended as a reference for health institutions in providing elderly exercise materials for elderly people with gout arthritis with impaired physical mobility